2007
DOI: 10.1080/17453670710014383
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of direct and indirect costs of internal fixation and cast treatment in acute scaphoid fractures: A randomized trial involving 52 patients

Abstract: There was a longer period of absence from work after cast than after surgery in manuals, but not in non-manuals. In non-manuals, total costs were lower after cast than after surgery. Socioeconomic classification had a greater influence on cost than mode of treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 19 publications
3
58
1
Order By: Relevance
“…The rate of loss to follow-up, reported in all studies, ranged from 0% to 26%. The authors of four of the eight studies clearly stated that their analysis was based on intention-to-treat principles 13,18,32,34 . The authors of three studies reported on cross-over to surgical treatment 18,32,33 ; however, Saedén et al 33 did not clearly state whether they performed an intention-to-treat analysis.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 4 more Smart Citations
“…The rate of loss to follow-up, reported in all studies, ranged from 0% to 26%. The authors of four of the eight studies clearly stated that their analysis was based on intention-to-treat principles 13,18,32,34 . The authors of three studies reported on cross-over to surgical treatment 18,32,33 ; however, Saedén et al 33 did not clearly state whether they performed an intention-to-treat analysis.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…In 2007, Vinnars et al 34 studied the data for a subgroup of fifty-two patients from the same randomized trial reported by Vinnars et al in 2008 18 . They included acute nondisplaced fractures of the scaphoid (Herbert type-A2, B1, B2, and B3 fractures).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations